Chapter: 'Introducing the U.S. Cyberlearning Community' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Marianne Bakia (Lecture Notes in Computer Science, 2016)
The term "Cyberlearning" is used in the United States to describe a community of researchers, largely funded by the US National Science Foundation, who are exploring the integration of computer science research with learning sciences research. The Cyberlearning community is parallel to the EC-TEL community and the purpose of this poster is to foster mutual engagement between the communities. The paper describes the origin of the term, the conception of the field, the kinds of research being conducted, and some of the exemplary projects. The paper will also introduce the Center for Innovative Research in Cyberlearning (CIRCL), which is the hub of the knowledge network (research community) for cyberlearning and hosts a useful collection of resources.